PENGARUH MEDIA SOSIAL, KEMANDIRIAN BELAJAR, PERAN ORANG TUA, FASILITAS BELAJAR DAN TEMAN SEBAYA TERHADAP PRESTASI BELAJAR SISWA PELAJARAN DASAR-DASAR PEMASARAN - Sagra Dwi Adinda; Rahmania, Meri; Selvia, Nisha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of social media, learning independence, parental role, learning facilities, and peers on students' academic achievement in the Basic Marketing subject of 10th grade students at SMK Negeri 2 Padang. The study employed a quantitative method with total sampling involving 108 students. Data were collected through questionnaires and analyzed using multiple linear regression. The results revealed that: (1) social media has a positive and significant effect on academic achievement; (2) learning independence has no significant effect; (3) parental role has a positive and significant effect; (4) learning facilities have a negative and significant effect; (5) peers have a negative and significant effect; (6) simultaneously, all independent variables influence academic achievement with a contribution of 18.7%. These findings suggest that parental support, proper use of social media, and adequate learning facilities are important to improve students’ achievement. Further research is recommended to expand variables and sample size.